Defining the genetic control of human blood plasma N-glycome using genome-wide association study. (11th March 2019) - Sharapov, Sodbo Zh; Tsepilov, Yakov A; Klaric, Lucija; Mangino, Massimo; Thareja, Gaurav; Shadrina, Alexandra S; Simurina, Mirna; Dagostino, Concetta; Dmitrieva, Julia; Vilaj, Marija; Vuckovic, Frano; Pavic, Tamara; et al.
Abstract: Glycosylation is a common post-translational modification of proteins. Glycosylation is associated with a number of human diseases. Defining genetic factors altering glycosylation may provide a basis for novel approaches to diagnostic and pharmaceutical applications. Here we report a genome-wide association study of the human blood plasma N-glycome composition in up to 3811 people measured by Ultra Performance Liquid Chromatography (UPLC) technology. Starting with the 36 original traits measured by UPLC, we computed an additional 77 derived traits leading to a total of 113 glycan traits. We studied associations between these traits and genetic polymorphisms located on human autosomes. We discovered and replicated 12 loci. This allowed us to demonstrate an overlap in genetic control between total plasma protein and IgG glycosylation. The majority of revealed loci contained genes that encode enzymes directly involved in glycosylation ( FUT3/FUT6, FUT8, B3GAT1, ST6GAL1, B4GALT1, ST3GAL4, MGAT3 and MGAT5 ) and a known regulator of plasma protein fucosylation ( HNF1A ). However, we also found loci that could possibly reflect other more complex aspects of glycosylation process. Functional genomic annotation suggested the role of several genes including DERL3, CHCHD10, TMEM121, IGH and IKZF1 . The hypotheses we generated may serve as a starting point for further functional studies in this research area.